Neu5Ac Induces Human Dental Pulp Stem Cell Osteo-/Odontoblastic Differentiation by Enhancing MAPK/ERK Pathway Activation. (23rd September 2021) - Li, Changzhou; Xie, Xinghuan; Liu, Zhongjun; Yang, Jianhua; Zuo, Daming; Xu, Shuaimei
Abstract : Dental pulp stem cells (DPSCs) must undergo odontoblastic differentiation in order to facilitate the process of dentin-pulp complex repair. Herein, we sought to explore the ability of Neu5Ac (one form of sialic acid) to influence DPSC osteo-/odontoblastic differentiation via modulating mitogen-activated protein kinase (MAPK) signaling. Methodology . DPSCs were isolated from human third permanent teeth and were grown in vitro. Fluorescent microscopy was used to detect the existence of sialic acid on the DPSC membrane. Following the treatment of different concentrations of Neu5Ac and removing sialic acid from the cell surface by neuraminidase, the osteo-/odontoblastic differentiation of these cells was evaluated via mineralization, alkaline phosphatase, and in vivo assays. In addition, the expression of genes related to osteo-/odontoblastic differentiation and MAPK signaling at different stages of this differentiation process was analyzed in the presence or absence of Neu5Ac. Results . The existence of sialic acid on the DPSC membrane was confirmed by fluorescent microscopy, and the ability of osteo-/odontoblastic differentiation was decreased after removing sialic acid by neuraminidase. Treatment of DPSCs with Neu5Ac (0.1 mM or 1 mM) significantly enhanced their mineralization ability and alkaline phosphatase activity. The expression levels of DMP1, DSPP, BSP, and RUNX2 were also increased. Treatment of nude mice with ManNAc (the prerequisite form of Neu5Ac) also enhanced DPSC mineralization activity in vivo. Furthermore, Neu5Ac treatment enhanced p-ERK expression in DPSCs, while ERK pathway inhibition disrupted the ability of Neu5Ac to enhance the osteo-/odontoblastic differentiation of these cells. Conclusions . Neu5Ac can promote DPSC osteo-/odontoblastic differentiation through a process associated with the modulation of the ERK signaling pathway activity.